PENGARUH PROFESIONALISME DAN PERILAKU DISFUNGSIONAL AUDITOR PADA KUALITAS AUDIT DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI - Baiq Armiana Malahayati; Maslichah Maslichah; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT This research was conducted to analyze the Effect of Professionalism and Auditor's Dysfunctional Behavior on Audit Quality with Job Satisfaction as a Moderating Variable ". The sample in this study is the Public Accountant Office (KAP) registered in Malang city The analytical method used is Multiple Linear Regression with SPSS 22 For Windows Software. Based on the results of hypothesis testing. simultaneously showing that simultaneous Professionalism, Auditor's Dysfunctional Behavior and Job Satisfaction Influence Audit Quality. Partially it shows that Auditor Professionalism and Dysfunctional Behavior Influence Audit Quality. The test results with job satisfaction variables as moderators show that Job Satisfaction Moderates the relationship between Professionalism and Audit Quality. Keywords : Professionalism, Auditor's Dysfunctional Behavior, Job Satisfaction, Audit Quality